Parental education and physical activity in pre‐school children. Issue 3 (15th April 2013) - Vale, S.; Ricardo, N.; Soares‐Miranda, L.; Santos, R.; Moreira, C.; Mota, J.
Abstract Background The purpose of this study was to objectively assess pre‐school children's total physical activity (TPA) patterns and compliance with guidelines and to examine differences relative to parental education. Methods The sample consisted on 509 healthy pre‐school children, aged 3–6 years recruited from kindergartens located in the metropolitan area of Porto, Portugal. The PA was assessed for 7 consecutive days by accelerometry. For TPA, we followed the guidelines of the National Association for Sport and Physical Education (NASPE) (children who spent at least >120 min per day in active play). For TPA, we calculated the proportion of children who spent at least >120 min per day in active play and moderate‐to‐vigorous physical activity (MVPA), we calculated the proportion of children who spent at least >60 min per day in active play. Parental education was analysed according to the Portuguese education system. Results Children with parents in the highest education level were less active than children from low and middle education level (P ≤ 0.001) in all patterns of PA (week and weekend). Regarding TPA during the week we found that the majority of children from low and middle parental education meet the NASPE guidelines. On the other hand, more than half the children from high parental education did not meet these recommendations (P ≤ 0.001) and MVPA recommendations (P ≤ 0.05). In both recommendations, children from low parental education were twice more likely to meet the recommendations compared with children belonging to high parental education. Conclusion Parent education was negatively associated with children's daily physical activity patterns and compliance with guidelines.